Analysis of Elementary School Students’ Language Ability in Facing Environmental Challenges: A Case Study at MI Raudlatul Ilmiyah Jakarta - Chaled, Mohammad Idham; Damanik, Prince Clinton Immanuel Christian; Husaeni, Rizki Achmad; Jayanti, Feri Dwi; Uli, Anastasia Arta (JIMU:Jurnal Ilmiah Multidisipliner, 2025)
This research aims to analyze the development of elementary school students' language skills, especially in the context of speaking, as well as the role of the social environment and teaching methods in shaping student communication at MI Raudlatul Ilmiyah, South Jakarta. Speaking ability is considered crucial as a means of socialization and achieving independence, and is strongly influenced by the social interaction environment which can shape the students' language variations. The challenge of the research location is the diverse background of students from upper-middle-class and lower-middle-class communities. The research method used is qualitative with a social experiment model. Data collection was carried out through questionnaires to measure students' understanding of language skills, direct observation of social interactions, and interviews with teachers and students. The research results indicate a development in the teacher's teaching methods from lectures to interactive techniques such as role play to develop students' imagination. Teachers demonstrate good language flexibility, able to switch between formal and informal/everyday language according to the class condition. In informal interactions outside the classroom (canteen and field), students tend to use casual everyday/non-standard language. However, there was a minor finding of instances where a small group of students in the corners of the classroom used inappropriate language. Generally, the questionnaire results show that students' language skills in socialization are very good, where students have the sensitivity and understanding to appropriately place the use of formal and non-formal language according to the communication context (with teachers, friends, or parents).